Prevalensi dan Karakteristik Buta Warna pada Populasi Urban di Jakarta - Syntia Nusanti; M. Sidik (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Purpose: To report the prevalence of color blindness in urban population in Jakarta Methods: This study is a part of the Urban Eye Health Study. Color vision examination was performed using Ishihara on adult and pediatric subjects with 6/6 vision. If incorrect reading was present, the examination was later continued by using Farnsworth Munsell Hue D 15, then proceeded with completing questionnaire. Results: The pediatric respondents in this study was 435 (6-16 years old). From that number of subjects, 5,97% of children had color blind. Meanwhile, the adult respondents (41-77 years old) in this study was 1040 with 3.26% of respondents had color blind. There were 100% of pediatric respondents diagnosed with congenital color blindness. Eighty-eight point twenty four percent of adult respondents were diagnosed with congenital color blindness while the remaining 11.76% were diagnosed with acquired color blindness. Conclusions: The prevalence of congenital color blindness in this study was 3,79%, as much as 88,24% from the adult group and 100% from the pediatric group.